Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1471-2458-14-741
|View full text |Cite
|
Sign up to set email alerts
|

Income-related inequalities in chronic conditions, physical functioning and psychological distress among older people in Australia: cross-sectional findings from the 45 and up study

Abstract: BackgroundThe burden of chronic disease continues to rise as populations age. There is relatively little published on the socioeconomic distribution of this burden in older people. This study quantifies absolute and relative income-related inequalities in prevalence of chronic diseases, severe physical functioning limitation and high psychological distress in mid-age and older people in Australia.MethodsCross-sectional study of 208,450 participants in the 45 and Up Study, a population-based cohort of men and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 41 publications
(57 reference statements)
2
25
0
Order By: Relevance
“…As for the association between income and functional limitations at older ages, recent analyses suggest a higher prevalence of impairment, disability and limitations among lower income groups 11 34. Similar to our results of the analysis of the most recent ESS wave (2014), the magnitude of these inequalities differed between countries, without showing a clear pattern among the different European regions 34.…”
Section: Discussionsupporting
confidence: 84%
“…As for the association between income and functional limitations at older ages, recent analyses suggest a higher prevalence of impairment, disability and limitations among lower income groups 11 34. Similar to our results of the analysis of the most recent ESS wave (2014), the magnitude of these inequalities differed between countries, without showing a clear pattern among the different European regions 34.…”
Section: Discussionsupporting
confidence: 84%
“…Cutler and colleagues (2009), for instance, were able to estimate that the improved treatments of the cardiovascular events accounted for 19 to 22 percent of the overall reduction in disability in the American older adults between 1984 and 1994. However, while disability and functional impairments may directly result from the complications of a wide variety of chronic health conditions, these conditions themselves are likely to be determined by the more upstream socio-economic and behavioral factors (Fors & Thorslund 2015;Korda et al 2014;Martin et al 2012;Minges et al 2011;Glover et al 2004). An accumulating body of international literature also documented a persistent socio-economic gradient in the prevalence and incidence of disability (Hosseinpoor et al 2013;Gubhaju et al 2015;Schoeni et al 2005;Sulander et al 2006;Huisman et al 2005;Huisman et al 2003), just as many other health indicators including chronic diseases were shown to be associated with social inequalities in older people (Fors & Thorslund 2015;Korda et al 2014).…”
Section: Key Findings and Interpretationsmentioning
confidence: 99%
“…It is well established that lower socioeconomic status, including education, is associated with poorer access to and outcome of health care in chronic conditions including PD, 26–29 even in Denmark 30 . The reasons may include a combination of behavioral, psychological, material, and social mechanisms 31–36 .…”
Section: Discussionmentioning
confidence: 99%